2019
DOI: 10.3389/fcell.2019.00108
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis: Inflammation Is a Necessary Evil

Abstract: Sepsis is one of the leading causes of deaths world-wide and yet there are no therapies available other than ICU treatment. The patient outcome is determined by a complex interplay between the pro and anti-inflammatory responses of the body i.e., a homeostatic balance between these two competing events to be achieved for the patient’s recovery. The initial attempts on drug development mainly focused on controlling inflammation, however, without any tangible outcome. This was despite most deaths occurring durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
215
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(221 citation statements)
references
References 141 publications
(153 reference statements)
4
215
0
2
Order By: Relevance
“…Maintaining balance between pro- and anti-inflammatory mechanisms is likely as important as a robust immune response. Cytokines are essential in initiating and augmenting the innate and adaptive immune response ( 42 ). Concomitant hyperinflammation has been linked to severe pulmonary dysfunction ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining balance between pro- and anti-inflammatory mechanisms is likely as important as a robust immune response. Cytokines are essential in initiating and augmenting the innate and adaptive immune response ( 42 ). Concomitant hyperinflammation has been linked to severe pulmonary dysfunction ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was thought that the host immune response to sepsis is characterized by an initial hyperinflammatory response, followed by an immunosuppressive phase as the disease progresses. However, recent studies have shown that both proinflammatory and anti-inflammatory responses occur early and simultaneously in sepsis [ 13 ]. In our study, genes in cluster A were found to be mainly involved in T-cell biology, antigen processing and presentation, and NK cell function.…”
Section: Discussionmentioning
confidence: 99%
“…These cytokines are known to be elevated as a result of cytokine storm due to the activation of innate immune cells, including macrophages during acute viral and bacterial infection (e.g., SARS-COV-2 infection (21,22), sepsis (23,24)), and BM and CT-MSCs (both OOT and CR products) may mitigate the hyperinflammation by inhibiting the cytokine response of macrophages (25,26). In T cell proliferation assay, OOT MSCs showed very low or no suppression as compared to CR MSCs for both BM and CT MSCs.…”
Section: Discussionmentioning
confidence: 99%